Working on a cognitive task does not influence performance in a physical fitness test. (July 2016) - Schücker, Linda; MacMahon, Clare
Abstract: Purpose: A limited number of studies have looked at the negative effect that cognitive fatigue has on physical performance. Methods and results: Two studies were conducted to assess the impact of a cognitive task on performance in an externally paced running task. In study 1, 12 trained athletes completed a standardized shuttle run, once after a cognitively fatiguing task (unmatched stroop for 10 min) and once after an easy cognitive task (matched stroop for 10 min). Performance in the shuttle run test did not differ between the two conditions, and, surprisingly, perceived effort was significantly higher in the control condition. In study 2, the control condition was modified and the easy cognitive task replaced by watching a video. 11 trained athletes completed both sessions, however, there were again no differences in either performance or in perceived effort. Conclusion: Both studies failed to reveal an impact of cognitive fatigue on subsequent physical performance. These findings contribute to the growing body of literature in this area, showing that the relationship between cognitive and physical task completion is not straightforward, and that other important factors still remain for investigation. Highlights: The effects of cognitive fatigue on physical performance are not straightforward. Cognitive fatigue does not influence performance in an externally paced task. Factors such as participant and task characteristics need to be further investigated.